An Application of Fuzzy Analytic Hierarchy Process in Risk Evaluation Model - Peng, Geng; Han, Lu; Liu, Zeyan; Guo, Yanyang; Yan, Junai; Jia, Xinyu (Frontiers in Psychology, 2021)
Conflicts in land exploration were incisive social problems which have been the subject of much research. Risk assessment of land conflicts is effective to resolve such problems. This work combined fuzzy mathematics and analytic hierarchy process (FAHP) together to assess risk in land conflicts which is useful to solve uncertainty and imprecision problems. Based on the analysis of the principles for the risk assessment of land conflicts index system, we present a set of risk assessment index using FAHP. The results shows that the overall risk is at low level, however, the risk of feasibility index and controllability index is at the middle level. The contribution of this paper reflects in two aspects: (1) the application of FAHP in risk assessments of land conflicts is effective; (2) it’s helpful for relevant departments to establish a strict management system of work safety for conflicts in land exploration based on the risk assessment results.